Pengembangan Program Kewirausahaan melalui Manajemen Pendidikan di SMK Amal Luhur Kota Medan - Haqki, Bay (Universitas Labuhanbatu, 2025)
This study aims to describe and analyze how educational management plays a role in the development of entrepreneurship programs at SMK Amal Luhur in Medan City. The background of this study is based on the importance of integrating entrepreneurial values in the education system, especially in Vocational High Schools (SMK) which are oriented towards producing graduates who are ready to work and are economically independent. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation studies. The results show that the development of the entrepreneurship program is carried out through a managerial process that includes entrepreneurship curriculum planning, implementation of project-based learning, and continuous evaluation involving teachers, students, and industry partners. In addition, the support of school leadership and collaboration with the business world are key factors in the success of the program. This study concludes that effective educational management can create a learning ecosystem that is conducive to the growth of students' entrepreneurial spirit.